Effect of peste des petits ruminants virus (PPRV) infection on the host immune response in naturally infected goats - DAS, S; CHOUDHURY, R; SULTANA, A; BALAMURUGAN, V; CHAKRAVARTY, I; DEVI, M; BORA, M; SHARMA, K (The Indian Journal of Animal Sciences, 2017)
Toll like receptors (TLRs) expressed by various immune cells and tissues are known to play an important role in recognising the pathogens by the host. The study was carried out to envisage the expression of virus-recognising-TLRs like TLR-3, TLR-7 and TLR-8 as well as the Th1 and Th2 cytokines in the serum of naturally Peste des petits ruminants virus (PPRV) infected goats. Goat serum samples, collected from three districts of Asom (Kamrup, Nalbari, Darrang), were screened for Peste des petits ruminants virus (PPRV) antibody by Complementary-ELISA. Out of 227 samples screened, 72 samples showed presence of PPR viral antibody with a percentage prevalence of 31.72%. Out of the positive samples, 39 were selected randomly for testing the TLR and cytokine response after PPRV infection. The study indicated TLR-8 to have an enhanced expression in serum of PPRV infected goats alongwith IL-12 and IFN-Î³ of the Th1 pathway. Further, in infected group, a significant correlation was registered between IL-12 and IFN-Î³. The present study showed the involvement of the Th-1 pathway in host immune response after PPRV natural infection which may help in proper disease management and control strategies.